Comparison of energy and nutrients intake in female adolescents with overweight and obesity - Pajuelo R., Jaime (2013)
Overweight and obesity result from change in dietary patterns and increasingly sedentary attitude. Objectives: To compare the energy and nutrient intake in female adolescents with overweight and obesity. Design: Cross-sectional, observational and analytical study. Location: Lima’s urban area Education Center. Participants: Adolescents aged 10 to 18 years. Interventions: One hundred overweight adolescents and 87 obese adolescents were studied. Diagnosis was done by body mass index (BMI) with the World Health Organization (WHO) reference population and cutoff levels between 85 and 95 percentile for overweight and over 95 for obesity. Amount of energy and nutrients was determined by a semi quantitative food frequency questionnaire using the Peruvian Table for Food Composition and the Table of the USA Department of Agriculture. FAO recommendations were used to determine the adequate percentage of energy and the quantitative identification of vitamin and mineral intake. Statistical analysis used Student t-test to compare measures. Main outcome measures: Energy intake, ingested nutrients, vitamins and minerals adequacy according to the study groups. Results: There was no difference in energy intake between the groups studied, and these values were lower than requirements. Adequacy of fat consumption, saturated, monounsaturated and polyunsaturated fats was below requirements; however saturated fat was more consumed. The amount of vitamins and minerals ingested covered requirements except for folates. Fiber intake was very poor. Conclusions: Neither group exceeded energy requirements, so it could be assumed that cause of these conditions was very little physical activity. On the other hand the main problem was dietary fiber, fat and folate intake deficiency.